2023
DOI: 10.3390/biology12071007
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Inhibits Yeast AMPK (Snf1) by Three Independent Mechanisms

Abstract: Snf1, the fungal homologue of mammalian AMP-dependent kinase (AMPK), is a key protein kinase coordinating the response of cells to a shortage of glucose. In fungi, the response is to activate respiratory gene expression and metabolism. The major regulation of Snf1 activity has been extensively investigated: In the absence of glucose, it becomes activated by phosphorylation of its threonine at position 210. This modification can be erased by phosphatases when glucose is restored. In the past decade, two additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…It was reported that plasma membrane P-type ATPase is a type of transport protein localized in the plasma membrane and is responsible for pumping hydrogen proteins from the cytoplasm to the extracellular space to maintain intracellular pH and ion homeostasis [7][8][9]. There are two plasma membrane H + -ATPases, PMA1 and PMA2, in fungi [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that plasma membrane P-type ATPase is a type of transport protein localized in the plasma membrane and is responsible for pumping hydrogen proteins from the cytoplasm to the extracellular space to maintain intracellular pH and ion homeostasis [7][8][9]. There are two plasma membrane H + -ATPases, PMA1 and PMA2, in fungi [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…According to the properties of its transport substances, the plasma membrane transport P-type ATPase can be divided into multiple subtypes, including sodium potassium pump (Na + /K + -ATPase), calcium pump (Ca 2+ -ATPase), proton pump (H + -ATPase), and heavy metal pump [5,6]. Among these subtypes, plasma membrane H + -ATPase is a type of hydrogen proton pump driven by ATP, which is responsible for pumping hydrogen protons from the cytoplasm to the extracellular space to maintain intracellular pH and ion homeostasis, form transmembrane electrochemical potential, and promote nutrient transportation and the expulsion of secondary metabolites [7][8][9]. Most fungi have two plasma membrane H + -ATPases, PMA1 and PMA2 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%